Immunogenicity of COVID ‐19 vaccines in patients with follicular lymphoma receiving frontline chemoimmunotherapy - Lim, YJ; Ward, V; Brown, A; Phillips, E; Kronsteiner, B; Malone, T; Jennings, D; Healy, S; Longet, S; James, T; Thomson, P; Farrell, L; et al. (Wiley, 2024)
Summary: Immune responses to primary COVID‐19 vaccination were investigated in 58 patients with follicular lymphoma (FL) as part of the PETReA trial of frontline therapy (EudraCT 2016–004010‐10). COVID‐19 vaccines (BNT162b2 or ChAdOx1) were administered before, during or after cytoreductive treatment comprising rituximab (depletes B cells) and either bendamustine (depletes CD4+ T cells) or cyclophosphamide‐based chemotherapy. Blood samples obtained after vaccine doses 1 and 2 (V1, V2) were analysed for antibodies and T cells reactive to the SARS‐CoV‐2 spike protein using the Abbott Architect and interferon‐gamma ELISpot assays respectively. Compared to 149 healthy controls, patients with FL exhibited lower antibody but preserved T‐cell responses. Within the FL cohort, multivariable analysis identified low pre‐treatment serum IgA levels and V2 administration during induction or maintenance treatment as independent determinants of lower antibody and higher T‐cell responses, and bendamustine and high/intermediate FLIPI‐2 score as additional determinants of a lower antibody response. Several clinical scenarios were identified where dichotomous immune responses were estimated with >95% confidence based on combinations of predictive variables. In conclusion, the immunogenicity of COVID‐19 vaccines in FL patients is influenced by multiple disease‐ and treatment‐related factors, among which B‐cell depletion showed differential effects on antibody and T‐cell responses.